PEMBUATAN SODIUM LIGNO SULFONAT (SLS) CHEMICAL INJECTION PADA PROSES EOR MINYAK BUMI DENGAN METODE SULFONASI MENGGUNAKAN LIMBAH KULIT KACANG TANAH - Nur Prasetyo Ponco Nugroho Nugroho (Jurusan Teknik Pertambangan Program Studi S1 Teknik Pertambangan Fakultas Teknik Pertambangan dan Perminyakan Universitas Papua, 2022)
Sodium lignosulfonate (SLS) is made by reacting lignin with the chemical compound Natium bisulfite (NaHSO3). In this study, lignin was processed from peanut shell waste, that is not economically valuable and tends to be garbage, into high economic value materials. The nutshells are dried, crushed and cooked in an autoclave (gaping vessel) then added Sodium bisulfite (NaHSO3). The use of temperature and pressure that has been varied in the autoclave and the continuous stirring process will produce a thick black liquid smelling pungent with acidic pH. To get a solution that has a neutral pH added NaOH drop by drop. After the pH is neutral, weigh the porcelain cup dry and clean, put the lignin liquid in the porcelain cup, weigh the lignin liquid along with the porcelain cup. Next, the lignin liquid along with the porcelain cup is heated in the oven until the lignin liquid is free from the water content. Once drying process in the oven is finished, the lignin solids in the porcelain cup are weighed. The mass of the weighing minus the mass of the porcelain cup results in the mass of the SLS produced.